Molecular characterization of black queen cell virus genotypes in Vietnam - Linh, Mai Thuy; Thu, Ha Thi; Duy, Nguyen Dinh; Quyen, Dong Van (Academia Journal of Biology, 2016)
Black queen cell virus (BQCV), a picorna-like honeybee virus, is one of the most common viral infections in honeybees. However, little is known about this virus infection in Vietnam. In this study, a partial helicase enzyme coding region (ORF1) was PCR amplified from three Apis cerana and three Apis mellifera BQCVs collected from honeybee colonies in different provinces of Vietnam, viz. Hung Yen, Bac Giang, Tien Giang, Dien Bien, Dong Nai, and Binh Phuoc. The PCR products were cloned into pCR2.1 vector and sequenced. The sequence analysis showed that the Vietnamese BQCV genomes were highly conserved and showed 97-100% identity. This suggests that the BQCV strains circulating in Vietnam are the same strain, however, they showed low (88-93%) similarity with BQCV strains in other countries . A phylogenetic tree based on the ORF1 region of 6 Vietnamese BQCVs was constructed, which were also compared with previously reported BQCV sequences derived from different countries. The result indicated that the Vietnamese BQCV strains and BQCV strains derived from Poland, Hungary, Austria formed one cluster, while and all Korean isolates formed a separate cluster, suggesting that BQCV strains in Vietnam may be originated from the European countries.